Fostering Readiness to Change through Work Engagement in Indonesian Government Organization - I Made Bayu Andika; Rina Anindita (Universitas Pendidikan Ganesha, 2023)
Organizational change has been widely examined by scholars. A readiness to change is essential to attain a success of the organizational change. Previous studies on readiness to change supported by employee’s engagement in government context are scarcity. Thus, this study aims to examine the relationship between the readiness to change and the employee’s engagement in religious affairs institution context. This study also investigates the relationship of those variables moderated by generation X and Y. The quantitative approach with survey research design was undertaken by administering a questionnaire to 179 civil servants under religious affairs institution online. The data was analyzed using PLS-SEM. The findings suggested that the employee’s work engagement and the process of change had a positive and significant relationship to the readiness to change. The work engagement had positive and significant relationship to the process of change and trust in the leadership. The trust in the leadership had positive and significant relationship to the process of change; however it did not have a relationship to the readiness to change. Moreover, generation X and Y did not moderate the relationship the work engagement and the readiness to change as well the process of change. The theoretical and managerial implications are discussed further.